Natural Selection of Glycoprotein B Mutations That Rescue the Small-Plaque Phenotype of a Fusion-Impaired Herpes Simplex Virus Mutant - Qing Fan (American Society for Microbiology, 2018)
ABSTRACT Glycoprotein B (gB) is a conserved viral fusion protein that is required for herpesvirus entry. To mediate fusion with the cellular membrane, gB refolds from a prefusion to a postfusion conformation. We hypothesize that an interaction between the C-terminal arm and the central coiled coil of the herpes simplex virus 1 (HSV-1) gB ectodomain is critical for fusion. We previously reported that three mutations in the C-terminal arm (I671A/H681A/F683A, called gB3A) greatly reduced cell-cell fusion and that virus carrying these mutations had a small-plaque phenotype and delayed entry into cells. By serially passaging gB3A virus, we selected three revertant viruses with larger plaques. These revertant viruses acquired mutations in gB that restore the fusion function of gB3A, including gB-A683V, gB-S383F/G645R/V705I/A855V, and gB-T509M/N709H. V705I and N709H are novel mutations that map to the portion of domain V that enters domain I in the postfusion structure. S383F, G645R, and T509M are novel mutations that map to an intersection of three domains in a prefusion model of gB. We introduced these second-site mutations individually and in combination into wild-type gB and gB3A to examine the impact of the mutations on fusion and expression. V705I and A855V (a known hyperfusogenic mutation) restored the fusion function of gB3A, whereas S383F and G645R dampened fusion and T509M and N709H worked in concert to restore gB3A fusion. The results identify two regions in the gB ectodomain that modulate the fusion activity of gB, potentially by impacting intramolecular interactions and stability of the prefusion and/or postfusion gB trimer. IMPORTANCE Glycoprotein B (gB) is an essential viral protein that is conserved in all herpesviruses and is required for virus entry. gB is thought to undergo a conformational change that provides the energy to fuse the viral and cellular membranes; however, the details of this conformational change and the structure of the prefusion and intermediate conformations of gB are not known. Previously, we demonstrated that mutations in the gB “arm” region inhibit fusion and impart a small-plaque phenotype. Using serial passage of a virus carrying these mutations, we identified revertants with restored plaque size. The revertant viruses acquired novel mutations in gB that restored fusion function and mapped to two sites in the gB ectodomain. This work supports our hypothesis that an interaction between the gB arm and the core of gB is critical for gB refolding and provides details about the function of gB in herpesvirus-mediated fusion and subsequent virus entry.